Decontamination of gnotobiotic mice experimentally monoassociated with Candida albicans. - Wagner, M (1975)
Gnotobiotic AKR mice, experimentally monoassociated with Candida albicans, were successfully decontaminated by oral treatment with amphotericin B incorporated in the drinking water. Germfree mice first were swabbed orally with viable C. albicans and then were allowed to acclimatize for 4 weeks. The log10 of number of C. albicans per gram of organ (with luminal contents) was 7.9 and 7.7 in the stomach and cecum, respectively. Direct fecal smears, as well as impresssion smears of stomach and cecum mucosal surfaces, revealed yeastphase cells, many with germ tubes, but no hyphal forms. No illness or mortality was observed over this period. The mice then were given amphotericin B DISsolved in the drinking water and offered ad libitum. At levels of 0.1 and 0.2 mg/ml, the number of fecal C. albicans was decreased but not eliminated completely. However, 0.3 mg/ml was sufficient to decontaminate the mice completely and return them to the germfree state. Residual amphotericin B was detected in the feces of the mice only while they were receiving the 0.3 mg/ml dose level. These mice remained germfree until the termination of the experiment, 10 weeks after the antibiotic had been discontinued and replaced by plain drinking water.